PENYEDIAAN WADAH SAMPAH DAUN KERING DI KP. TEGALEGA PERMAI - Syaiful, Syaiful; Permana, Arisandi Anwar; Aminda, Renea Shinta; Afrianto, Yuggo (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2024)
Litter is defined by man by his degree of dress, in the natural processes there is in reality no such thing as garbage, only products produced after and during the natural process. However, since in human life it is defined by the concept of the environment. At this time the problem with my neighborhood was that there were no garbage cans available for the runoff of dry leaves that would pollute the streets. Since there were trees in my neighborhood and there were not small in number, after I had noticed that the leaves had not been burned or discarded by the janitors, the dried leaves were simply collected with trashbag plastic and stored next to the street. And every week a janitor picks up the garbage to the treatment of the dried leaf litter for organic fertilizer. The results of this study produced a plan to provide incredibly efficient dry leaf shelters, in order to create a clean environment and to eliminate long-term dry leaf containers.